2018
DOI: 10.3847/1538-4357/aaa776
|View full text |Cite
|
Sign up to set email alerts
|

The Variable Fast Soft X-Ray Wind in PG 1211+143

Abstract: The analysis of a series of seven observations of the nearby (z = 0.0809) QSO PG 1211+143, taken with the Reflection Grating Spectrometer (RGS) onboard XMM-Newton in 2014, are presented. The high-resolution soft X-ray spectrum, with a total exposure exceeding 600 ks, shows a series of blueshifted absorption lines from the He and H-like transitions of N, O, and Ne, as well as from L-shell Fe. The strongest absorption lines are all systematically blueshifted by −0.06c, originating in two absorption zones from lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 86 publications
(154 reference statements)
7
34
0
Order By: Relevance
“…A similar scenario was also recently suggested for the fast outflow in the quasar PG 1211+143 (Reeves et al 2018b). Here, the fast wind consists of a two phase (low and high ionization) clumpy medium, where the smaller, denser low ionization clumps may account for the rapid variations in the soft X-ray absorbing gas on timescales of days.…”
Section: Properties Of the Soft X-ray Absorbersupporting
confidence: 81%
See 2 more Smart Citations
“…A similar scenario was also recently suggested for the fast outflow in the quasar PG 1211+143 (Reeves et al 2018b). Here, the fast wind consists of a two phase (low and high ionization) clumpy medium, where the smaller, denser low ionization clumps may account for the rapid variations in the soft X-ray absorbing gas on timescales of days.…”
Section: Properties Of the Soft X-ray Absorbersupporting
confidence: 81%
“…The nearby (z = 0.0809) non-BAL QSO PG 1211+143, which has a well established Xray ultra fast outflow (Pounds et al 2003;Pounds & Reeves 2009;Reeves et al 2018b), has recently been found to have a broad UV absorption trough, blueshifted with respect to Lyα by −17, 000 km s −1 (Kriss et al 2018a). This is consistent with the blue-shift (of −0.06c) of the soft X-ray absorber, as measured in contemporary X-ray grating observa-tions (Reeves et al 2018b;Danehkar et al 2018) with XMM-Newton RGS and Chandra HETG, as well as with the velocity at iron K (Pounds et al 2016). In PG 1211+143, the UV mini-BAL trough also appears to be variable and is not detected in all of the epochs analyzed by Kriss et al (2018a).…”
Section: The Link Between Uv Bals and X-ray Ultra Fastmentioning
confidence: 99%
See 1 more Smart Citation
“…Reanalysis of this same data set reaffirmed the detection of ultra-high-velocity gas, but at −0.14±0.01c, with additional high-ionization lines at approximately −0.07c (Pounds 2014). Most recently, the deepest observations to date of PG 1211 +143 using XMM-Newton (∼450 ks) in 2014 again detected ultra-high-velocity gas at −0.129c and high-velocity gas at −0.066±0.003c (Pounds et al 2016b;Reeves et al 2018). The UFO at −0.129c is not seen in contemporaneous NuSTAR data (Zoghbi et al 2015), but a combined analysis of the XMMNewton and NuSTAR spectra show that the spectral structure around 7 keV is quite complex.…”
Section: Discussionmentioning
confidence: 65%
“…Subsequent analysis of the 2014 XMM-Newton RGS data by Reeves et al (2018) shows that two lower-ionization, lowervelocity absorbers are also present with velocities of −0.062± 0.001c (v out = −18,600 ± 300 km s ) and −0.059±0.002c (v out = −17,700 ± 600 km s −1 ), the latter of which is a good match to the −17,300 km s −1 (−0.0577c) warm absorber we detect in our Chandra spectrum. However, the absorber we detect is slightly lower in ionization (log x = -+ 2.87 0.10 0.32 versus log ξ=3.4±0.1), and nearly an order of magnitude lower in column density (N H = 3 × 10 21 cm −2 versus 1 × 10 22 cm −2…”
Section: Discussionmentioning
confidence: 99%